1992
DOI: 10.1021/ac00036a004
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet and light absorption spectrometry

Abstract: with a B S In 1961, an M.S. in 1963. and a Ph D. in 1964. spent a year as a Postdoctoral Research Associate at Purdue University, and |olned the faculty at UNO in 1965. His present research Interests Include ultraviolet and light absorption spectrometry, reaction-rate analyses, heteropolymoiybdate chemistry, and on-line computer applications to chemical problems. He has authored or coauthored numerous research papers, an Instrumental analysis laboratory manual, an introductory analytical chemistry textbook, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 114 publications
0
2
0
1
Order By: Relevance
“…5 Since derivative techniques have been widely applied: further development [6][7][8] and reviews were reported. [9][10][11][12][13][14][15][16][17] The main targets of reviews 17 were basic characteristics of DS and a few analytical applications of DS were given (The number of bibliographic references was 93).…”
mentioning
confidence: 99%
“…5 Since derivative techniques have been widely applied: further development [6][7][8] and reviews were reported. [9][10][11][12][13][14][15][16][17] The main targets of reviews 17 were basic characteristics of DS and a few analytical applications of DS were given (The number of bibliographic references was 93).…”
mentioning
confidence: 99%
“…[17][18][19][20][21][22] Meanwhile, several multi-component determinations of inorganic substances based on the application of these methods to spectrophotometric data have been reported. [23][24] The main goal of the present report is developing a simple and proper method for simultaneous spectrophotometric monitoring of iron and cobalt traces in different water samples by using PAN as a sensitive chelating agent together with chemometric approaches such as PC-ANN, PCR and PLS. In the PC-ANN model the scores of the principal component analysis (PCA) of the response data of the calibration mixture were used as an input layer.…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, a compilação de espectros de absorção sob a forma de atlas ou bases de dados é usada para: i) identificação e verificação do grau de pureza de compostos; ii) cálculo da diferença de energia entre estados electrónicos e do momento dipolar da transição. O desenvolvimento da espectroscopia de absorção UV-Vis tem sido constante ao longo dos últimos anos, sendo a técnica revista em número especial da revista Analytical Chemistry, de dois em dois anos, desde 1945 [24].…”
Section: Espectroscopia Na Região Do Ultravioleta-visível (Uv-vis)unclassified